Plant surface signal sensing and infection-related morphogenesis of Colletotrichum orbiculare. (March 2023) - Kodama, Sayo; Bissaro, Bastien; Berrin, Jean-Guy; Kubo, Yasuyuki
Abstract: Several plant pathogenic fungi including Colletotrichum species form specialized cells called appressoria to directly penetrate the intact cuticles of their host plants. These appressoria-forming fungi can infect a wide range of plant species including many commercially important fruits, vegetables, and cereals. The differentiation of appressorium relies on the detection and transduction of physical and biochemical signals present on the plant surface. Working with the cucumber anthracnose fungus Colletotrichum orbiculare, our research has revealed that long chain aliphatic molecules produced through the hydrolysis of plant surface cuticle by conidial cutinase serves as signaling molecules. Following signal detection, the morphogenesis related NDR (nuclear dbf2-related) kinase pathway, and its downstream transcription factor Co MTF4, play a crucial role in the transduction of plant-derived signal involved in appressorium development. In the stage of plant penetration from appressoria, we have also uncovered the recognition of plant surface signals mediated by a pair of peroxidase/copper radical oxidase (CRO) enzymes. The corresponding pair of genes conserve tandem localization in the genome of most Colletotrichum species and the enzyme pair is co-secreted during the penetration stage. The oxidative action of the paired enzymes on plant cuticular derived long-chain alcohols generates signaling molecules (i.e., aldehydes) that potentially functions in a biochemical cascade. In this article, we review our current understanding of fungal-plant communication in adapting to the environmental conditions required for infection-related morphogenesis. Highlights: In Colletotrichum orbiculare, sensing and transduction of plant surface signals is required for differentiation of appressoria. The morphogenesis related NDR kinase pathway is crucial for biochemical signal transduction for appressorium development. A tandem of metalloenzymes oxidizes cuticle to generates signaling molecules that drives a biochemical cascade for plant penetration. There are two phases in fungal-plant communication for adapting environmental condition during C. orbiculare infection.